PKM Edukasi Menulis Gagasan Pokok dan Gagasan Pendukung Berbasis Fenomena Sampah untuk Meningkatkan Literasi SDGs Siswa Sekolah Dasar - Mikhael Klemens Kedang; Siddik Romadhan; Blandina Seko Bani (Fakultas Sosial dan Ilmu Politik Universitas Wiraraja, 2026)
One of the global issues in achieving the Sustainable Development Goals (SDGs) in education and environmental sustainability is waste management. In the educational context, students’ ability to understand and communicate environmental issues through literacy activities remains relatively low. This Community Service Program (PkM) aimed to improve students’ SDGs literacy through education on writing main ideas and supporting ideas based on waste-related phenomena.The program employed an experiential learning approach consisting of four stages: (1) introducing students to environmental issues related to the types, impacts, and management of waste (concrete experience); (2) identifying organic and inorganic waste (reflective observation); (3) discovering creative products made from waste materials (abstract conceptualization); and (4) practicing paragraph writing containing main ideas and supporting ideas based on the previous activities (active experimentation). The target participants were fourth-grade students of SD Sikumana 2 in Kupang City, East Nusa Tenggara (NTT). The results of the community service activity showed that students were able to understand the concepts of main ideas and supporting ideas more effectively through contextual and experience-based learning. Most students succeeded in composing coherent, well-structured, and environmentally relevant paragraphs. In addition, students demonstrated increased ecological awareness through maintaining school cleanliness and identifying simple forms of waste management.Therefore, this activity was effective in integrating language literacy and environmental literacy based on the SDGs in elementary school learning. The implications of this activity highlight the importance of strengthening contextual and environment-based learning to develop students’ literacy skills and environmental awareness from an early age.